Hotels' dependency on online intermediaries and their chosen distribution channel portfolios: Three country insights. (January 2016) - Stangl, Brigitte; Inversini, Alessandro; Schegg, Roland
Graphical abstract: Abstract : Highlights: Traditional sales channels are still highly relevant while the importance of social media as an actual sales channel is marginal. Differences with regards to penetration and dependency on OTAs between the different countries are detected. The amount of OTAs used as intermediary varies between 0 and 15—the average amount is 3.61. Four distribution channel mix strategies are revealed: multichannel-, electronic-, real time-, and traditional distributors. The strategy profiles show differences between the countries and concerning various characteristics of the SMEs (e.g., their target group). Abstract: New intermediaries are entering the market, challenging the hospitality industry to find an appropriate distribution channel portfolio. This research investigates how many channels hotels in Austria, Germany and Switzerland choose and what role the various channels play. Findings based on 1014 questionnaires reveal an average mix of 8.06 offline and online channel categories. Traditional channels, such as walk-ins and telephone, still play a major role; however, about one fifth of the bookings are completely generated online. On average, 3.61 online travel agencies (OTAs) are used. With regards to OTA penetration, an oligopolistic market structure is prevalent. Swiss and German hotels' OTA dependency is higher than Austrian's. A series of a posteriori cluster analysis results in four distribution portfolio groups hoteliers choose: multi-channel-, electronic-, real time-, and traditional distributors. Distribution portfolio profiles facilitate learning from strategies used by hotels with certain characteristics such as target group and star-rating.